"Where the Computer Cannot Reach—Is Dreaming”: The Imaginary & (In)visible Worlds - Foley, Amy (Atlantis, 2025)
This article explores the work of Janelle Monáe through, and with, the words and images offered by Ruha Benjamin in Imagination: A Manifesto, arguing that these and other Afrofuturist texts provide us with tools for reconceptualizing the visible world as dense, textured, and never wholly legible, consumable, or commodifiable. This essay asks us to dwell, to practice a temporary suspension, in the visualizations offered by these artists, as they invent new fictions for us to inhabit – fictions that work against the dominant narrative of visibility that says we can be made fully readable and comprehensible to power through proliferating mechanisms of technological surveillance. This false but enduring narrative, which often feels deceptively natural and inescapable, works to infantilize and depoliticize imagination, to thwart creative disruption, and to produce collective despair. While this essay acknowledges the very real, violent power entwined within this fiction – and the need to, at times, use this very narrative as a shield for survival in the present – it also argues that we must simultaneously recognize this as fiction and create new fictions so as to open ourselves to a future in which survival and flourishing are not contingent on complicity in the constrictive narratives that frame us today. As we are shaped in both the real and the imaginary, this essay contends, projecting new fictions is a crucial practice for making more liveable futures.